Physician’s Undecided Attitudes towards Posthumous Reproduction: Fertility Preservation in Cancer Patients with a Poor Prognosis - Quinn, Gwendolyn P. (J Support Oncol, 2012)
BACKGROUND: The American Society for Clinical Oncology (ASCO) established guidelines for fertility preservation for cancer patients. In a national study of US oncologists, we examined attitudes towards the use of fertility preservation among patients with a poor prognosis, focusing on attitudes towards posthumous reproduction. METHOD: A cross-sectional survey was administered via mail and Internet to a stratified random sample of US oncologists and measured demographics, knowledge, attitude, and practice behaviors regarding posthumous reproduction and fertility preservation with cancer patients of childbearing age. RESULTS: Only 16.2% supported posthumous parenting, while the majority (51.5%) did not have an opinion. ANOVA analyses indicated attitudes towards posthumous reproduction were significantly related to physician practice behaviors and dependent on oncologists’ knowledge of ASCO guidelines. CONCLUSIONS: Physician attitudes may conflict with following recommended guidelines and may reduce the likelihood that some patients receive information about fertility preservation. Further education may raise physicians’ awareness of poor prognostic patients’ interest in pursuing this technology.